Evaluation of combined famotidine with quercetin for the treatment of peptic ulcer: in vivo animal study - Abourehab MA; Khaled KA; Sarhan HA; Ahmed OA (Dove Medical Press, 2015)
Mohammed AS Abourehab,1,2 Khaled A Khaled,1 Hatem AA Sarhan,1 Osama AA Ahmed1,3 1Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Minia University, Minia, Egypt; 2Department of Pharmaceutics, Faculty of Pharmacy, Umm Al-Qura University, Makkah, Saudi Arabia; 3Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, King Abdulaziz University, Jeddah, Saudi Arabia Abstract: The aim of this work was to prepare a combined drug dosage form of famotidine (FAM) and quercetin (QRT) to augment treatment of gastric ulcer. FAM was prepared as freeze-dried floating alginate beads using ion gelation method and then coated with Eudragit RL100 to sustain FAM release. QRT was prepared as solid dispersion with polyvinyl pyrrolidone K30 to improve its solubility. Photo images and scanning electron microscope images of the prepared beads were carried out to detect floating behavior and to reveal surface and core shape of the prepared beads. Anti-ulcerogenic effect and histopathological examination of gastric tissues were carried out to investigate the effect of the combined drug formulation compared with commercial FAM tablets and FAM beads. Gastric glutathione (GSH), superoxide dismutase, catalase, tissue myeloperoxidase, and lipid peroxidation enzyme activities and levels in rat stomach tissues were also determined. Results revealed that spherical beads were formed with an average diameter of 1.64±0.33 mm. They floated immediately with no lag time before floating, and remained buoyant throughout the test period. Treatment with a combination of FAM beads plus QRT showed the absence of any signs of inflammation or hemorrhage, and significantly prevented the indomethacin-induced decrease in GSH levels (P<0.05) with regain of normal GSH gastric tissue levels. Also, there was a significant difference in the decrease of malondialdehyde level compared to FAM commercial tablets or beads alone (P<0.05). The combined formula significantly improved the myeloperoxidase level compared to both the disease control group and commercial FAM tablet-treated group (P<0.05). Formulation of FAM as floating beads in combination with solid dispersion of QRT improved the anti-ulcer activity compared to commercially available tablets, which reveals a promising application for treatment of peptic ulcer. Keywords: anti-ulcerogenic effect, biochemical studies, floating beads, histopathological examination